Active Learning in Online Courses: An Examination of Students' Learning Experience - Kevin Floyd; Johnathan Yerby; Terry Smith; Alex Koohang (International School for Social and Business Studies, 2012)
This study examines students' perception toward their learning experience inan e-learning environment where active learning through regular and routinegraded discussion activities/assignments is expected. Attention was given tothe variables of age; gender; increased experience with online courses; andincreased proficiency with the course management system. Gender was foundto be a significant factor with regard to students' perception toward theirlearning experience in online courses. Discussion is carried out based on theresults of the study. The discussion then shifts to a focus upon strengtheningactive learning in online courses and common ways in which active learningcan be used effectively in online courses. Conclusions and recommendationsfor future research complete the paper.